Chapter Aspetto verbale e referenza nominale - Gebert, Lucyna (Biblioteca di Studi Slavistici, 2016)
The paper attempts to examine the relation between the verbal aspect in the Slavic languages and the referential status of nominal arguments of the predicate. As is well known, Slavic languages (except Bulgarian and Macedonian) have not developed articles as a grammatical category. It is suggested that in addition to the well-known means of conveying referential information in these articleless languages - such as word order, use of demonstrative/indefinite pronouns, restrictive relative clauses, case alternations and prosody - the verbal aspect also should be taken into account.